Amplification characteristics in active tapered segmented cladding fiber with large mode area. (21st June 2021) - Xie, Caijian; Ning, Tigang; Zheng, Jingjing; Pei, Li; Wang, Jianshuai; Li, Jing; You, Haidong; Wang, Chuangye; Gao, Xuekai
Abstract: A kind of tapered segmented cladding fiber (T-SCF) with large mode area (LMA) is proposed, and the mode and amplification characteristics of T-SCFs with concave, linear, and convex tapered structures are investigated based on finite-element method (FEM) and few-mode steady-state rate equation. Simulation results indicate that the concave tapered structure can introduce high loss for high-order modes (HOMs) that is advantageous to achieve single-mode operation, whereas the convex tapered structure provides large effective mode area that can help to mitigate nonlinear effects. Meanwhile, the small-to-large amplification scheme shows further advantages on stripping off HOMs, and the large-to-small amplification scheme decreases the heat load density induced by the high-power pump. Moreover, single-mode propagation performance, effective mode area, and heat load density of the T-SCF are superior to those of tapered step index fiber (T-SIF). These theoretical model and numerical results can provide instructive suggestions for designing high-power fiber lasers and amplifiers.